Kabbalah and catastrophe: historical memory in premodern Jewish mysticism - Lachter, Hartley (Stanford studies in Jewish mysticism, 2024)
"While premodern kabbalistic texts were not chronicles of historical events, they provided elaborate models for understanding the secret divine plan guiding human affairs. Hartley Lachter analyzes innovative kabbalistic doctrines, such as the idea of reincarnation and the notion of multiple successive universes, through which Jewish mystics sought to demonstrate that the misfortunes of Jewish history were in fact necessary steps toward redemption. Lachter argues that these works, mostly composed between the early 14th century and the generation affected by the Spanish expulsion in the early 16th century, enabled Jewish readers to make sense of the troubling misfortunes of their own time. Kabbalah and Catastrophe uncovers the remarkable variety of ways that kabbalists deployed esoteric tradition to argue that God had not abandoned the Jews to the inscrutable forces of history. Instead, they suggested to readers that Jews are history's primary actors, and that despite their small numbers and lack of military power, Jews nonetheless secretly push history forward. For scholars of Jewish mysticism and medieval Jewish history, Lachter articulates how premodern mystical texts can be crucial sources of insight into how Jews understood the meaning of history"